Hyperemesis gravidarum severity, enteral tube feeding and cardiometabolic markers in offspring cord blood. Issue 12 (28th December 2022) - Nijsten, Kelly; Koot, Marjette H.; Bais, Joke M. J.; Ris-Stalpers, Carrie; van Eekelen, Rik; Bremer, Henk A.; van der Ham, David P.; Heidema, Wieteke M.; Huisjes, Anjoke; Kleiverda, Gunilla; Kruizenga, Hinke; Kuppens, Simone M.; et al.
Abstract: This study aimed to investigate the association between hyperemesis gravidarum (HG) severity and early enteral tube feeding on cardiometabolic markers in offspring cord blood. We included women admitted for HG, who participated in the MOTHER randomised controlled trial (RCT) and observational cohort. The MOTHER RCT showed that early enteral tube feeding in addition to standard care did not affect symptoms/birth outcomes. Among RCT and cohort participants, we assessed how HG severity affected lipid, c-peptide, glucose and free thyroxine cord blood levels. HG severity measures were severity of vomiting at inclusion and 3 weeks after inclusion, pregnancy weight gain and 24-h energy intake at inclusion, readmissions and duration of hospital admissions. Cord blood measures were also compared between RCT participants allocated to enteral tube feeding and those receiving standard care. Between 2013-2016, 215 women were included: 115 RCT and 100 cohort participants. Eighty-one cord blood samples were available. Univariable not multivariable regression analysis showed that lower maternal weight gain was associated with higher cord blood glucose levels ( β : –0·08, 95% CI –0·16, –0·00). Lower maternal weight gain was associated with higher Apo-B cord blood levels in multivariable regression analysis ( β : –0·01, 95% CI –0·02, –0·01). No associations were found between other HG severity measures or allocation to enteral tube feeding and cord blood cardiometabolic markers. In conclusion, while lower maternal weight gain was associated with higher Apo-B cord blood levels, no other HG severity measures were linked with cord blood cardiometabolic markers, nor were these markers affected by enteral tube feeding.